From Epidemic to Pandemic: Effects of the COVID-19 Outbreak on High School Program Choices in Sweden - Aino-Maija Aalto; Dagmar Müller; J. Lucas Tilley (Institute of Labor Economics (IZA), 2022)
We study whether the onset of the COVID-19 crisis affected the program choices of high school applicants in Sweden. Our analysis exploits the fact that the admission process consists of two stages: a preliminary round in which applicants initially rank programs in order of preference and a final round in which they can alter their preliminary rankings. In 2020, the timing of the two rounds happened to provide a unique pre- and post-crisis snapshot of applicants' field-of-study choices. Using school-level data on applicants' top-ranked programs for all admission rounds between 2016 and 2020, we implement a difference-in-differences method to identify the immediate effect of the crisis on demand for programs. We find no change in demand for academic programs, but a decline in top-ranked applications to some of the vocational programs. The declines are most pronounced and robust for several service-oriented programs, in particular those related to the hotel and restaurant sector, which was the most adversely affected industry during the crisis. This finding suggests that labor market considerations influence the study choices made by relatively young students.
Keywords: I20; J24; 330; COVID-19; business cycle; human capital investment; field of study